KEUNGGULAN YANG MEMBERDAYAKAN: MENGUNGKAP KEHADIRAN PARA PEMIMPIN PEREMPUAN MUSLIM YANG BERDAMPAK DI LINGKUNGAN LEMBAGA PENDIDIKAN TINGGI INDONESIA - Komalasari, Rita; Mustafa, Cecep (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This literature review aims to examine the presence and impact of Muslim women in administrative roles at the Indonesian ITE. The results show that the leadership structure at the Indonesian Institute of Teacher Education is quite intricate. Transactional, transformational, laissez-faire, democratic, and autocratic techniques are all used by Muslim women in positions of power. As their effects on leadership skills and abilities show, these styles have a strong positive link with leadership efficiency. Understanding the many facets of effective leadership is facilitated by incorporating Islamic leadership ideals, particularly Performance and Islamic Leadership values. The study also identifies several mediating factors—leadership ethos, goals and responsibilities, interpersonal correspondence, professional development, and employee empowerment—that affect leadership efficacy in ITEs. A developed Leadership Effectiveness Model synthesizes the research findings, offering a structured framework for Muslim women leaders to adapt their leadership approaches according to contextual challenges and opportunities. In conclusion, this study contributes novel insights by exploring the impactful presence of Muslim women leaders within the Indonesian Institute of Teacher Education. The study's findings provide valuable guidance for Muslim women leaders' career progression and effectiveness, ultimately contributing to the broader discourse on gender equality and empowerment in leadership positions.